Technologies of Identity: The Language of the Incontinent Body in Margaret Laurence’s The Stone Angel - Pennee, Donna Palmateer (Studies in Canadian Literature, 2000)
The irrevocable contradiction of Enlightenment values with the invader/settler history of Canada is interrogated in Margaret Laurence's The Stone Angel through ideas of class, gender, race, and imperialism. Hagar Shipley's respected social position is contingent upon her colonialist ancestry, even as her rebellion (through marriage to the socially inferior "other" Brampton Shipley) deprives her of paternal approbation and inheritance. Thus her physical incontinence is inscribed socially, both as symbol of the impropriety of the lower orders in the community hierarchy, and as the self-denied but felt inferiority of the transplanted Anglo class itself, "people…so desperately uncertain of their own worth and their ability to cope within their own societies" that they seek to impose a Eurocentric hierarchy on the New World. The incontinent body can be read for its condensations and displacements of technologies of identity.